SELF EFFICACY BERHUBUNGAN DENGAN KEJADIAN DEPRESI LANSIA - Pereira, Dirce Rosa; Putri, Ronasari Mahaji; Rosdiana, Yanti (Universitas Tribhuwana Tunggadewi, 2021)
There is a phenomenon that there is a decrease in Activities Daily Living (ADL) and an increase in the incidence of depression in the elderly. This phenomenon is associated with the quality of life of the elderly which will worsen if there is no effort to minimize it. This study aims to determine the relationship between self-efficacy and depression in the elderly. It is an observational study with a cross-sectional design. The population was all elderly in Panti Werdha Pangesti Malang with the criteria for elderly aged 60-74 years, had a history of depression, the patient's family had no history of depression, totaling 62 people. A sample of 54 people was taken using the Slovin formula, with simple random sampling technique. The self-efficacy instrument of daily living activity in the form of a questionnaire was adopted from the General Self-Efficacy Scale (GSE) questionnaire, while the depression instrument used the Geriatric Depression Scale (GDS) questionnaire. Statistical test using the Fisher Exact Test. The results showed that almost all elderly people had low self-efficacy, almost all elderly experienced mild depression. Statistical tests show that there is a relationship between self-efficacy and depression (P value 0.05). It is recommended for further researchers to add biological, genetic and psychological factors as part of the determinants of depression.